A School-based Suicide Prevention Programme with Peer Support to Prevent Suicidal Ideation in Adolescents: A Cross-Sectional Study - Rohmi, Faizatur; Agustiningsih, Nia; Setiawan, Arik Agung; Supriono (Universitas STRADA Indonesia, 2026)
Background: Suicide is a significant public health concern among school-aged adolescents. Suicidal ideation (SI) in adolescents are robustly associated with greater risk of concurrent and succeeding suicide attempts. Evidence suggests that suicidal ideation in adolescents is influenced by peer support at school. Purpose: Our aim was to investigate the influence of peer support on school-based suicidal ideation in adolescents. Methods: A cross-sectional study was conducted in Malang, Indonesia. A total of 179 Adolescents aged 13-15 years were recruited from six classes at junior high schools in Malang by stratified random sampling. An anonymous self-report questionnaire was used to collect demographic characteristics, suicidal ideation, and peer support. Logistic regression was used to test the hypotheses. Results: The results of the multiple logistic regression showed that peer support and protection against suicidal ideation had a significance value of 0.008. This means that peer support influences protection against suicidal ideation. The results also showed that peer support and suicide vulnerability had a significance value of 0.840. This means that peer support did not influence vulnerability to suicidal ideation. Conclusions: Suicide vulnerability is a risk factor for suicidal ideation. Peer support can enhance protective factors against suicidal ideation. Public health nurses can collaborate with school nurses to regularly detect symptoms of suicidal ideation and provide early intervention. Educating peers and teachers about methods to enhance protective factors in adolescents can be beneficial in reducing suicidal ideation.